Seasonal variation in preference for green roof vegetation - Thorpert, Petra; Ode Sang, Åsa; Buffam, Ishi (Frontiers in Ecology and Evolution, 2024)
Green roofs are vegetation systems that are particularly well-suited to dense urban environments, and can contribute multiple ecosystem services that support biodiversity, human health, and well-being. Several health benefits are dependent on the way that people perceive the characteristics of the vegetation on the green roof, that is, their environmental appraisal. In this study we set out to explore the effects of different types of green roof vegetation, along with seasonal and successional variations, on visual aesthetical experiences, as well as perceived biodiversity. An online photo elicitation survey was conducted using standardised photographs of a selection of green roofs in Malmö, Sweden, during three different seasons. In the survey, members of the public were asked to evaluate different aesthetic qualities, and to estimate biodiversity and the stress reducing capacity for each photograph. Results showed statistical differences among roof types and by season and successional stage in terms of perceived colour, perceived biodiversity, aesthetic quality, and restorative effects, where the observed differences in perceived values were largely driven by the colour frame of the green roof. Lower scores were associated with a high percentage of red or brown-red shades (p<0.001), while higher scores were associated with a high percentages of green or white (p<0.001). The results of the study therefore have the potential to inform green roof management strategies.